Characteristics and reasons for diabetic-defaulters between primary care clinics and diabetic specialist clinic: A prospective cohort study in Kuantan, Pahang - Abdullah, Fa’iza; Tin, Myo Han; Md Aris, Mohd Aznan; Osman, Iskandar Firzada (2016)
Defaulted appointment in diabetic clinics is a great concern as it affects disease controlled and complications. Geographical location, clinic-types and quality of health services provided are known determinant reasons for default between diabetic-patients at public-primary-care-clinic (PPCCs) and public-hospital-diabetic-specialist-clinic (DS-OPD).